Purtscher-Like Retinopathy Secondary to Medication Induced Calcium-Alkali Syndrome and Acute Pancreatitis in a Pregnant Female. (17th November 2022) - Alaei, Ravin; Shen, Carl; Chan, Brian J.; Martin, James
ABSTRACT: Purpose: To report a case of Purtscher-like retinopathy secondary to acute pancreatitis caused by medication-induced calcium-alkali syndrome in a pregnant woman. Methods: Case report Results: A 39-year-old 23-week pregnant patient complained of visual disturbances during admission for acute pancreatitis precipitated by calcium-alkali syndrome. History revealed the acute ingestion of over 2, 400 mg of elemental calcium from over the counter medication in the background of longstanding use. Visual acuity was counting fingers at 1 foot bilaterally. Posterior segment exam revealed Purtscher-flecken in the posterior pole with scattered dot hemorrhages. Optical coherence tomography (OCT) revealed inner retinal thickening and increased hyper-reflectivity. OCT angiography demonstrated loss of flow primarily in the superficial capillary plexuses. The patient was diagnosed with Purtscher-like retinopathy and observed. Two months follow up revealed resolution of the funduscopic findings and visual acuity improved minimally to 20/200 in the right eye and counting fingers in the left eye. Conclusion: Common over the counter medication can potentiate a calcium-alkali syndrome capable of causing a Purtscher-like retinopathy.